Constraints on triggered seismicity and its control on permeability evolution - Derek Elsworth; Ziyan Li; Pengliang Yu; Mengke An; Fengshou Zhang; Rui Huang; Zihan Sun; Guanglei Cui; Tianyu Chen; Quan Gan; Yixin Zhao; Jishan Liu; et al. (Journal of Rock Mechanics and Geotechnical Engineering)
Triggered seismicity is a key hazard where fluids are injected or withdrawn from the subsurface and may impact permeability. Understanding the mechanisms that control fluid injection-triggered seismicity allows its mitigation. Key controls on seismicity are defined in terms of fault and fracture strength, second-order frictional response and stability, and competing fluid-driven mechanisms for arrest. We desire to constrain maximum event magnitudes in triggered earthquakes by relating pre-existing critical stresses to fluid injection volume to explain why some recorded events are significantly larger than anticipated seismic moment thresholds. This formalism is consistent with several uncharacteristically large fluid injection-triggered earthquakes. Such methods of reactivating fractures and faults by hydraulic stimulation in shear or tensile fracturing are routinely used to create permeability in the subsurface. Microearthquakes (MEQs) generated by such stimulations can be used to diagnose permeability evolution. Although high-fidelity data sets are scarce, the EGS-Collab and Utah FORGE hydraulic stimulation field demonstration projects provide high-fidelity data sets that concurrently track permeability evolution and triggered seismicity. Machine learning deciphers the principal features of MEQs and the resulting permeability evolution that best track permeability changes – with transfer learning methods allowing robust predictions across multiple eological settings. Changes in permeability at reactivated fractures in both shear and extensional modes suggest that permeability change (Δk) scales with the seismic moment (M) of individual MEQs as Δk∝M. This scaling relation is exact at early times but degrades with successive MEQs, but provides a method for characterizing crustal permeability evolution using MEQs, alone. Importantly, we quantify for the first time the role of prestress in defining the elevated magnitude and seismic moment of fluid injection-triggered events, and demonstrate that such MEQs can also be used as diagnostic in quantifying permeability evolution in the crust.